Agile Leadership and AI Tool Acceptance: The mediating role of trust in AI technology - Doan, Huy Hoang; Tran, Thi My Linh (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This study was conducted to understand how Agile Leadership affects employees' acceptance of artificial intelligence (AI) tools in the workplace, with Trust in AI Technology examined as a mediating variable. A quantitative survey method was used, with data collected from 127 employees working at organizations that have implemented AI. Data were analyzed using structural equation modeling (SEM). The results show that a flexible leadership style enhances trust in AI technology and increases employees' willingness to adopt AI tools in their daily work. These findings contribute to the theory of leadership and technology acceptance, provide some practical suggestions for managers looking to effectively integrate AI into their organizations.